Pedot/Graphene/Nickel-Nanoparticles Composites as Electrodes for Microbial Fuel Cells - Gacitua-Santalices, M; Gacitua-Santalices, M (Springer New York LLC, 2019)
This paper presents a new direct electron transfer based glucose/oxygen microbial fuel cell (MFC), whose operating ability has been tested in presence of Escherichia coli (E. coli). A stainless steel electrode was modified to produce an anode. In the first step, electropolymerized film of poly (3,4-ethylenedioxythiophene) (EDOT), nickel nanoparticles (np-Ni) and thermally reduced graphene (TrGO) were used and subsequently reduced to electrochemical reduced graphite oxide (ErGO). Morphological characterization of the anode shows a homogeneous distribution of the Ni nanoparticles and ErGO over the electrode surface. Subsequently, characterization of the films allow to observe an increase in the output power and enhancement biocompatibility between microorganism and modified electrode. Performance of the MFCs is estimated through in situ potential and power generation over time curves using E. coli cultures feed with glucose as the substrate. The PEDOT|ErGO|np-Ni anode displayed an absolute power and maximum power density of 3.9 ± 0.3 mW and 0.32 mW cm−2 respectively, with an internal resistance of 1630 Ω, a 30% enhancement when compared to the PEDOT|ErGO anode. © 2019, Springer Science+Business Media, LLC, part of Springer Nature.